Superficial gastric neoplasm: Regarding 28 observations - Sojo, Enrique; Estapé, Gonzalo; Falconi, Luis; De Los Santos, Julio (Cirugía del Uruguay, 1979)
The authors analyze 28 cases of superficial gastric neoplasm which had excellent evolution following surgery. They also point out the change in concept because diagnosis should be established, with substitution of the old "clinical - radiologic" criteria for the "clínical histologic radiologic-endoscopic" approach. Evolution of gastric cancer befare it, to an advanced stage is show. Numerous symptoms and signs should induce the physician to suspect the presence of a neoplasm, though in no case should diagnosis be stablished on such basis. Several radiologic complementary techniques are required and double contrast is of considerable value in detecting small lesions or those double contrast detecting small lesions or those located in barely accesible positions where conventional methods fail. Considerable advance has been achieved by fibroendoscopy with directed biopsy, for this method has attained 96 % success in diagnosis of cases studied.